Assessment on surface treatment on fatigue life of cylinder block for linear engine using frequency response approach - Rahman, Md. Mustafizur; Mohd. Ihsan, Ahmad Kamal Ariffin; Abdullah, Shahrir; Mat Noor, Muhamad; Abu Bakar, Rosli; Maleque, Md. Abdul (Science Publications, 2009)
Objectives: This study was focused on the finite element techniques to investigate the effect of surface treatment on the fatigue life of the vibrating cylinder block for new two-stroke free piston engine using random loading conditions.